(untitled) (Hungarian Journal of Industry and Chemistry, 2002)
In whole effluent toxicity (WET) testing the aggregate toxicity of an effluent is measured, using different test organisms. Although these predicted deleterious effects will occur in natural (real-world) ecosystems, the tests are performed in the laboratory, under strictly controlled conditions. However, there are many reasons why these test results cannot be directly applied for real-world ecosystems. One basic problem is that exposure changes with space and time. Several physical, chemical and biological processes can result in significant decreases in exposure concentrations of a test substance over time. For many industrial effluents biodegradation is perhaps the most important process which affects the environmental concentration of the test substance. Biodegradation is a specific process as not only appropriate abiotic conditions are necessary but also a competent bacterial population, both anaerob and aerob should be established. Our main goal was to assess how toxicity of a selected industrial effluent changes over time, caused by degradation. In order to measure the aggregate toxicity of the effluent the ToxAlert®100 luminometer was used, developed by Merck. This test is in compliance with ISO/EN/DIN 11348. The use of the bioluminescent bacterium Vibrio fischeri (or other bacteria) has several advantages comparing to conventional toxicity testing. The test is rapid and causes no ethical problems. Our results has shown that toxicity changes caused by degradation can be appropriately followed by bioluminescent bacteria.